(untitled) (Medical Forum Monthly, 2024)
Hepatocellular carcinoma (HCC) is the most common primary liver cancer and a leading cause of cancer-related deaths worldwide. The prognosis for patients with unresectable HCC remains poor, highlighting the urgent need for more effective first-line treatments. The basic aim of this review is to find the efficacy and safety of tislelizumab plus lenvatinib as first-line treatment in patients with unresectable hepatocellular carcinoma. This review analysis was conducted at College of Medicine and Health Sciences, National University, Oman during 2020 to 2024. A comprehensive literature review was conducted to evaluate the efficacy and safety of tislelizumab plus lenvatinib as a first-line treatment for patients with unresectable hepatocellular carcinoma (HCC). Multiple electronic databases, including PubMed, Embase, and Cochrane Library, were systematically searched for relevant studies. The search terms included combinations of keywords such as "tislelizumab," "lenvatinib," "hepatocellular carcinoma," "HCC," "unresectable," "first-line treatment," "immunotherapy," and "targeted therapy." Additional sources, such as conference proceedings and clinical trial registries, were also reviewed to identify unpublished data. The combination of tislelizumab and lenvatinib offers a promising first-line treatment option for patients with unresectable HCC, demonstrating significant improvements in overall survival and progression-free survival with a manageable safety profile.